Coronary plaque morphology and characteristics in patients with raised haemoglobin A1c: an intravascular ultrasound Study - Ahmed Mostafa Ahmed; Wael Anwar Haseeb; Reda Biomy Bastawisy; Mohammed Kamal Salama (Journal of the Pakistan Medical Association, 2023)
Objectives:To identify coronary plaque morphology using grey scale and virtual histology intravascular ultrasound in patients with and without elevated glycated haemoglobin. Methods: The cross-sectional study was conducted at the Cardiology Department of Kafrelsheikh University, Egypt, from November 2019 to January 2022, and comprised adult patients of either gender suffering from acute coronary syndrome admitted for catheterisation. The patients were divided into three groups.Diabetic patients were in group A, prediabetic patients with elevated glycated haemoglobin in group B, and patients with normal glycated haemoglobin in group C. All patients were subjected to clinical examination, 12-lead electrocardiogram, coronary angiography and multimodality intravascular ultrasonography scan of proximal segments 3-6cmof non-culprit coronary arteries intra group differences were compared using the analysis of variance (ANOVA) test. Continue..